2021
DOI: 10.3389/fcell.2021.699304
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ferroptosis Pathway by Ubiquitination

Abstract: Ferroptosis is an iron-dependent form of programmed cell death, which plays crucial roles in tumorigenesis, ischemia–reperfusion injury and various human degenerative diseases. Ferroptosis is characterized by aberrant iron and lipid metabolisms. Mechanistically, excess of catalytic iron is capable of triggering lipid peroxidation followed by Fenton reaction to induce ferroptosis. The induction of ferroptosis can be inhibited by sufficient glutathione (GSH) synthesis via system Xc– transporter-mediated cystine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 178 publications
(206 reference statements)
0
10
0
Order By: Relevance
“…In addition, other pathways related to intracellular stress (i.e. autophagy and protein ubiquitination) have been detected by IPA analysis confirming the activation and presence of ferroptosis in DU145 cells treated with RSL3 + FAC [ 25 , 26 ] (Fig. S3 ).…”
Section: Resultsmentioning
confidence: 63%
“…In addition, other pathways related to intracellular stress (i.e. autophagy and protein ubiquitination) have been detected by IPA analysis confirming the activation and presence of ferroptosis in DU145 cells treated with RSL3 + FAC [ 25 , 26 ] (Fig. S3 ).…”
Section: Resultsmentioning
confidence: 63%
“…Free Fe 2+ is transported into the cytoplasm by DMT1, participating in the formation of LIP, or being stored with FTH1 ( Figure 6 ). Subsequent LPO is provoked by excessive iron either by the iron-mediated Fenton reaction to produce ROS and capture hydrogen atoms from PL-PUFAs, or activating enzymes containing iron (for example, lipoxygenases) ( 26 , 27 ). As a radical-trapping antioxidant ( 28 ), Fer-1 is identified from screenings as potent ferroptosis inhibitors, and its activity lies in its capability to slow down the accumulation of lipid hydrogen peroxide ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…By applying GO and KEGG, we confirmed that the gene that is co-expressed with ACSL4 is remarkably enriched in the pathway that is linked to protein ubiquitination. According to the findings of many research reports, the process of ubiquitination has a role in the modulation of the ferroptosis pathway (24). Recent research has shown that the protein BAP1 reduces the degree of histone 2A ubiquitination affinity to the promoters of the ferroptosis suppressor gene SLC7A11, which in turn suppresses the expression of SLC7A11 in a deubiquitinating-dependent way (25).…”
Section: Discussionmentioning
confidence: 99%